Hak Asuh Anak Akibat Perceraian dalam Pandangan Ulama Pedesaan - Ila Nurmila; Azmi Azizah; Robi Awaludin (Istinbath | Jurnal Penelitian Hukum Islam, 2020)
One of the purposes of marriage is to form a sakinah, mawaddah, warahmah family. However, in the course of family life does not always run smoothly sometimes encounter obstacles, not infrequently the problems and disagreements between husband and wife ended in divorce. And divorce is a very bitter drug that is only used to treat household diseases that can not be maintained again so there is no drug other than a divorce that can cure it. Divorce can deliver the status of the child that becomes the obligation of husband or wife. The breakup of marriage due to divorce will result in various consequences, both for wife, husband, especially for children. Divorce raises questions about the continuity of education maintenance and the financing of children's needs. This condition is very interesting for a writer to know more about child custody as a result of divorce and how also according to the opinion of a cleric of Karangampel Village District of Baregbeg Regency of Ciamis.